Edukasi dan Pemberdayaan Masyarakat Dalam Pemanfaatan Eco Enzyme Sebagai Solusi Pengelolaan Sampah Organik Rumah Tangga - Azzahra Anissa Waheeda; Resvika Yendri; Hidayati Taporuk; Elvina Safitri; Finna Amelia Putri; Muhammad Rayhan; Windy Pristika Putri; Dini Astari; Afzahul Rahmi; Gusni Rahma; Oktri Warman (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
The problem of household organic waste remains an environmental challenge that requires sustainable solutions. One management innovation is the use of eco-enzymes, a liquid produced by fermenting organic waste that can be used as a fertilizer, cleaner, and disinfectant. This community service activity aims to improve community knowledge and attitudes regarding the use of eco-enzymes as a household waste management effort. The methods used included interactive outreach, eco-enzyme production demonstrations, and the distribution of educational leaflets. The activity was carried out in July 2024 in Jorong Aro Sawah Ujung, Nagari Talang, Gunung Talang District, Solok Regency, with 22 participants. Evaluation was conducted using pre-test and post-test questionnaires. The results of the activity showed an increase in community knowledge from 76.7% before the intervention to 95.8% after the intervention, as well as an increase in positive attitudes from 65% to 75%. This activity successfully equipped the community with basic skills in processing organic waste into useful products while raising awareness of the implementation of the zero-waste concept. Thus, this program has the potential to be replicated as a model for community-based organic waste management.